Three different methods for ZnO-RGO nanocomposite synthesis and its adsorption capacity for methylene blue dye removal in a comparative study - Safaa A. Hussein; Gharib M. Taha; F. A. Adam; Marwa A. Moghazy (BMC Chemistry)
Abstract Water is one of the vital needs of life. However, due to rapid industrialization, urbanization and lack of awareness, the world population now facing the threat of water shortage. To ensure that future living conditions are preserved, it is crucial to reduce water pollution and protect the ecosystem. Zinc oxide- reduced graphene oxide (ZnO-RGO) nanocomposite is used in this study as an adsorbent for the adsorption of methylene blue (MB) dye from an aqueous solution. An easy strategy was used for the synthesis of reduced graphene oxide nanoparticles (RGO), Zinc oxide nanoparticles (ZnO) and ZnO-RGO nanocomposite. The synthesis of reduced graphene oxide (RGO) was accomplished through the exothermic reaction of a modified Hummer's method. In a novel approach, zinc oxide nanoparticles (ZnO NPs) were synthesized using the green Leidenfrost technique. This study presents a comparative investigation of ZnO-RGO nanocomposite synthesis employing both green and chemical methods. Three distinct approaches were utilized to prepare the ZnO-RGO nanocomposite: (1) the innovative Leidenfrost green method for composite A1, (2) a chemical precipitation method for composite A2, and (3) a physical mixing sonication method for composite A3. This research marks the first application of the Leidenfrost technique in the synthesis of ZnO-RGO nanocomposites, contributing to the growing body of knowledge in this field. X-ray diffraction (XRD), Burnauer-Emmett-Teller (BET), Fourier transform infrared (FTIR), Zeta potential, transmittance electron microscope (TEM) and scanning electron microscope (SEM) analyses are conducted for synthesized sample characterization. Comparing the XRD patterns of the three synthesis methods, it is notable that the intensity peaks of composite A3 were the highest when ZnO was synthesized using a green method, indicating a higher degree of crystallinity. FTIR analysis approves that combining ZnO with RGO affects the functional groups of the three nanocomposite surfaces. The SEM analysis shows ZnO NPs and RGO sheets are incorporated together. In the case of A1 composite sharp angles make a flower shape was observed due to the unique synthesizing method. The surface area for A2 composite is the highest (7.29 m2/g) compared with A1 (2.91 m2/g) and A3(1.90 m2/g). A comparison study is made among the three nanocomposites for MB dye removal. The effect of adsorbent dose, pH, contact time and initial dye concentration on dye adsorption has been studied. The results show that A1 and A2 nanocomposites removed 85.5 and 87.5% of MB at the optimum adsorbent dose of 0.15 g/100 ml at pH8 and A3 removed 95% of MB at the optimum dose of 0.1 g/100 ml at pH 2. All three composites exhibited adherence to the Langmuir isotherm model, with correlation coefficients (R2) of 0.9858, 0.9904, and 0.9959 for A1, A2, and A3, respectively. Kinetic study results demonstrated that the pseudo-second-order model best described the adsorption process for all three composites, yielding R2 values of 0.9998, 0.9988, and 1.0000 for A1, A2, and A3, respectively. The A3 nanocomposite shows the highest adsorption capacity (104.5 mg/g) compared to the other composites (87.7 and 97.5 mg/g for A1 and A2, respectively). Desorption experiments revealed that the dye removal percentages varied with the ratio of the ethanol–water mixture used. Absolute ethanol achieved a 90% removal compared with 1:1 and 1:2 aqueous ethanol solutions (87.5% and 80%, respectively).